A comparative study in learning curves of laparoscopic lateral suspension vs. laparoscopic sacrocolpopexy: preliminary results - Malanowska-Jarema, Ewelina; Osnytska, Yana; Starczewski, Andrzej; Balzarro, Matteo; Rubilotta, Emanuele (Frontiers in Surgery, 2023)
Determination of the learning curve of new techniques is essential to improve safety and efficiency. Limited information is available regarding learning curves of different techniques in laparoscopic pelvic floor surgery.The aim of this study was to compare the learning curve of two operative techniques, laparoscopic lateral suspension (LLS) and laparoscopic sacrocolpopexy (LSC).We conducted a prospective study to assess the learning curve of LLS and LSC by implementing a structured urogyneacological surgical training with the use of pelvic trainers among urogynecology fellow. The fellow was an experienced urogynecologic surgeon, however laparoscopic suturing and dissection naive at the beginning of the study. She was required to assist in 20 laparoscopic urogyneacologic surgeries and undertake laparoscopic suturing and knot tying training with mesh positioning on a laparoscopic trainer for 4 h/wk during the trial period. After the completion of this structured training program, the fellow performed LLS and LSC under the supervision of experienced subspecialist as the primary surgeon. To compare data of LLS and LSC learning curves, linear regression analysis was used. Subjective pre- and post-operative evaluation of POP and pelvic floor disorders was undertaken preoperatively and 12 months postoperatively using the PFDI-20 -Quality of Life validated questionnaire Follow-up was scheduled 12 months after the surgery and performed by a skilled urogynecologist. Objective cure was defined as POPQ stage < II in any compartment Results Mean operative time of laparoscopic sacrocolpopexy was 168,26 min and 160,33 min for lateral suspension respectively. According to linear regression analysis after 43 procedures the learning curve for LLS was shorter than for LSC (OP Time 134,69 min). In both groups there was a significant reduction in bothersome POP (P ≤ 0.005). Two bladder injuries and one lumbar pain were recorded during the study. Overall objective success at 12 months was 90,7 % for LSC and 89,1 % for LLS, respectively. The LLS could be an alternative to the LSC in the treatment of POP with its good objective and subjective outcomes. LLS has a shorter learning curve and it is technically less demanding than LSC.